(untitled) (Polis (Santiago), 2018)
The author claims that the current teaching / learning does not prepare students to handle the growing complexity of the environment nor its more aggressive and competitive character, and retrieves the liberating specificity of education, now framed by a mechanistic scheme. It is alarming to see -it notes- that the educational task is as much and more schooling than the old schools at the turn of the century. We need to restore education in an holistic perspective and consider that all educational activity involves proactive and creative subjects. It proposes, then, to learn to move in the world of uncertainty.